Uji Performa Waterjet Thruster Produk 3D Printing Material Super Tought Polylactic Acid Terhadap Gaya Dorong - Marcellino Stevanus Seva; Hasdiansah Hasdiansah (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2024)
In the world of transportation, there are many things that must be considered, ranging from safety to efficiency. Propulsion system planning is very important, this is because the system is a thrust generator that will determine the performance of the ship. The thrust generated must be able to overcome the resistance or friction of the ship with water. In recent times, many studies have been conducted to improve the performance and efficiency of the waterjet thruster. In this research, the performance of the waterjet thruster will be tested with variations in the number of inlet blades and the number of turbo outlet blades. The levels used are 8 blades and 15 blades. The manufacturing process on waterjet thruster components such as inlet, impeller, and turbo outlet uses Fused Deposition Modeling (FDM) technology to obtain high dimensional accuracy. From the research conducted, it can be concluded that the number of blades at the turbo inlet and outlet has a major effect on the thrust generated. The turbo outlet has a greater role than the inlet in influencing the thrust force. From the research conducted by Nori and this study, it can be concluded that the turbo outlet with 8 blades produces the highest thrust force compared to 6 blades and 15 blades.